The interaction between vaginal microbiota, cervical length and vaginal progesterone treatment for preterm birth risk - Kindinger,LM; Bennett,PR; Lee,YS; Marchesi,JR; Smith,A; Cacciatore,S; Holmes,E; Nicholson,JK; Teoh,TG; MacIntyre,DA (Microbiome, 2017)
Background:Preterm birth is the primary cause of infant death worldwide. A short cervix in the second trimester of pregnancy is a risk factor for preterm birth. In specific patient cohorts, vaginal progesterone reduces this risk. Using 16S rRNA gene sequencing we undertook a prospective study in women at risk of preterm birth(n=161) to assess 1) the relationship between vaginal microbiotaand cervical length in the second trimester and preterm birth-risk, and 2) the impact of vaginal progesterone on vaginal bacterial communities in women with a short cervix.Results:Lactobacillus iners dominance at 16 weeks gestation was significantly associated with both a short cervix <25mm (n=15, P<0.05), andpreterm birth <34+0 weeks (n=18, 38P<0.01; 69% PPV).In contrast, L. crispatus dominance was highly predictive of term birth (n=127, 98% PPV). Cervical shortening and preterm birthwere not associated with vaginal dysbiosis. A longitudinal characterization of vaginal microbiota (<18, 22, 28 and 34 weeks)was then undertaken in women receiving vaginal progesterone (400mg/OD, n=25) versus controls (n=42).Progesterone did not alter vaginal bacterial community structurenor reduce L. iners-associated preterm birth (<34 weeks). Conclusions:L. iners dominance of the vaginal microbiota at 16 weeks gestation is a risk factor for preterm birth, whereas L. crispatus dominance is protective against preterm birth. Vaginal progesterone does not appear to impact the pregnancy vaginal microbiota. Patients and clinicians who may be concerned about ‘infection risk’ associated with use of a vaginal pessary during high-risk pregnancy can be reassured.